POSTPARTUM ACUYOGA SEBAGAI PELUANG USAHA MANDIRI BIDAN DI ERA MILLENIAL PRODI KEBIDANAN CURUP TAHUN 2020: POSTPARTUM ACUYOGA - Farida Esmianti Esmianti; Kurniyati Kurniyati; Wenny Indah Purnama Eka; Lydiya Sipahutar (LPPM Universitas Al Muslim, 2021)
The paradigm of midwifery services at this time has experienced a shift where the high public interest in quality midwifery services demands midwifery service innovation and creativity from midwives. Many forms of entrepreneurship from the Midwife's Independent Practice are an option for midwives to increase the types of complementary midwifery services holistically (Body, mind and Spirit) to reduce medical interventions during pregnancy and postpartum, one of which is postpartum acuyoga, a combination of acupressure and yoga. The purpose of this community service is to provide information on knowledge and skills about postpartum Acuyoga to alumni of the Curup Midwifery Study Program who already have a Midwife Practice License. The method used in this community service is a workshop which is carried out for 3 days including the activities on the first day, namely the delivery of material about the independent business opportunities of midwives and Postpartum Acuyoga followed by the second day, namely the practice of Postpartum Acuyoga. This activity went smoothly and was attended by 30 midwives, where all participants were able to participate in the activity for 3 days without any obstacles. Participants understand the importance of innovating in developing midwifery services so that they can increase their income and experience in entrepreneurship.